The use of discarded sweet potato tuber as feed on egg production, egg quality and blood parameter of laying hen - Moonsrikaew, Sonthaya; Pulma, Chusak; Jaichansukkit, Teerapong; Aeuplang, Kanokvan (RMUTSB ACADEMIC JOURNAL, 2022)
Discarded sweet potato tubers (SPT) were abundant and cheap. This research aimed to study effects of the use of SPT as feed for feeding laying hen on egg production, egg quality and blood parameters. The research was conducted by a completely randomized design (CRD) using 41-week-old of Lohmann brown laying hens of 150 in total. The experiment was divided into 5 treatments, the pigment negative control feed formulated based on cassava chip meal (CM), positive control feed formulated based on ground corn (C), and the corn replace with SPT at 50, 75 and 100 percentage (SPT50, SPT75 and SPT100, respectively). It was found that the hen-day-egg production and egg mass of SPT50 and SPT75 had significantly higher than SPT100, while feed conversion ratio was signiticantly lower than C (P<0.05). The albumin height, Haught unit, yolk index and shell thickness of all treatments were not significantly different (P>0.05), but the CM gave the lowest egg production, egg mass and yolk color (P<0.05), but the blood parameters of all treatments were not significantly different. Therefore, the SPT could totally replace cassava meal or replace 50 and 75 percentage of ground corn without having any negative effects on egg production, egg quality and hen blood parameters. Besides, the SPT had potential source of color in the yolk similar as corn, and reduced the feed cost by 4.71 baht per kilogram of egg.